Political Border Issues in Africa - Al-Najjar, Ashour Masoud ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2016)
This research highlights a critical geographical and political issue concerning the African continent: the consequences of colonial border demarcation during the 19th and early 20th centuries. Territories were divided according to the interests of European colonial powers, with little regard for the geographic continuity of African tribes—many of which practiced nomadic herding. This division disrupted traditional movement and land use, and led to the creation of numerous landlocked states lacking access to coastlines, thereby hampering their economic development. The arbitrary borders also gave rise to ongoing disputes between African countries, some escalating into armed conflicts. The study presents examples of these issues, noting that over one-third of Africa’s borders were drawn as straight geometric lines aligned with meridians and parallels, with no consideration for the interests of local populations.